2021
DOI: 10.1186/s12885-021-09010-0
|View full text |Cite
|
Sign up to set email alerts
|

High expression of eIF4E is associated with tumor macrophage infiltration and leads to poor prognosis in breast cancer

Abstract: Background The expression and activation of eukaryotic translation initiation factor 4E (eIF4E) is associated with cell transformation and tumor initiation, but the functional role and the mechanism whereby it drives immune cell infiltration in breast cancer (BRCA) remain uncertain. Methods Oncomine, Timer and UALCAN were used to analyze the expression of eIF4E in various cancers. PrognoScan, Kaplan–Meier plotter, and GEPIA were utilized to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…The expression of EIF4E were overexpressed in various cancer types and interrelated with a worse outcome in multiple cancer [30]. EIF4E was found related to several cancers, such as breast cancer [31], prostate cancer [32] and skin squamous cell carcinoma [33]. Consistent with our ndings, Jiang et al reported that EIF4E expression was overexpressed in HCC samples and cell lines, and its overexpression was an independent predictor for overall survival and disease-free survival [34].…”
Section: Discussionsupporting
confidence: 88%
“…The expression of EIF4E were overexpressed in various cancer types and interrelated with a worse outcome in multiple cancer [30]. EIF4E was found related to several cancers, such as breast cancer [31], prostate cancer [32] and skin squamous cell carcinoma [33]. Consistent with our ndings, Jiang et al reported that EIF4E expression was overexpressed in HCC samples and cell lines, and its overexpression was an independent predictor for overall survival and disease-free survival [34].…”
Section: Discussionsupporting
confidence: 88%
“…In the ARG-ST1 and ARG-ST2 subtypes with good prognosis, tumour suppressor immune cell infltration, for instance, B cells [38] and CD4 + T cells [39], was observed to be considerably increased. Moreover, the infltration of cancer-promoting immune cells, for example, M2 macrophages, was also increased simultaneously [40,41]. Tis fnding is not entirely consistent with previous studies.…”
Section: Discussionsupporting
confidence: 48%
“…The upregulation of inhibitory costimulatory signaling in response to inflammatory cytokines (66) and the integrated stress response (ISR) (81) are prime examples. Altered eIF4E levels also impact the immune infiltration of breast tumors (82). Here we uncover an additional player that negatively impacts the upregulation of PD-L1 in response to the tumoricidal, proinflammatory cytokine IFNgamma.…”
Section: Discussionmentioning
confidence: 99%